A Locus Linked to p16 Modifies Melanoma Risk in Dutch Familial Atypical Multiple Mole Melanoma (FAMMM) Syndrome Families - van der Velden, Pieter A.; Sandkuijl, Lodewijk A.; Bergman, Wilma; Hille, Elysée T.M.; Frants, Rune R.; Gruis, Nelleke A. (Genome Research, 1999)
The CDKN2A gene that encodes the cell cycle inhibitor p16 shows mutations in many but not all 9p21-linked melanoma families. Most Dutch melanoma families segregate for a unique founder mutation (p16-Leiden), encoding a truncated nonfunctional p16 protein. The highly variable risk for p16-Leiden carriers to develop melanoma suggests a role for other genetic and/or environmental factors. We hypothesized that a 9p21 gene other than CDKN2A may be relevant in the remaining 9p21-linked melanoma families without p16 mutations but may also act as a risk modifier in p16-Leiden carriers. Haplotype analysis for 9p21 was performed using microsatellite markers in six p16-Leiden families originating from a founder population. p16-Leiden carriers in two families shared an unexpectedly large founder haplotype (∼20-cM) around CDKN2A, mostly in proximal direction. Melanoma-positive p16-Leiden carriers from these families showed this extensive proximal haplotype compared with melanoma-negative p16-Leiden carriers from the same families. Additional p16-Leiden families less heavily affected with melanoma showed shorter haplotypes sharing, excluding the region proximally of CDKN2A. The presence of a gene involved in melanoma susceptibility proximal of CDKN2A is corroborated by somatic deletions of 9p in tumors, which frequently do not include CDKN2A but a more proximal chromosomal area instead. Our results provide a candidate region for further gene mapping in p16-negative 9p21-linked melanoma families and guide the search for risk modifiers in melanoma development.